(untitled) (International Journal of Environmental Sciences, 2024)
Guduchi (Tinospora Cordifolia Willd.) is one of the most important medicinal plants described in Ayurveda and is widely known for its Rasayana, Jwaraghna, Tridoshahara, Deepana, Pachana, and immune-supportive actions. It is traditionally used for promoting strength, improving resistance against disease, supporting metabolic functions, and maintaining general health. In modern scientific understanding, Tinospora Cordifolia has shown immunomodulatory, antioxidant, anti-inflammatory, hepatoprotective, antidiabetic, antimicrobial, and adaptogenic activities. Several experimental and review studies report that its stem and other parts may influence cellular and humoral immunity, macrophage activity, cytokine response, antioxidant defense, and host resistance. In Ayurveda, Guduchi is mainly indicated in conditions involving impaired Agni, weak Bala, chronic fever, Pitta disorders, Rakta vitiation, metabolic disturbance, and lowered vitality. Its Rasayana action helps in nourishment of Dhatu, improvement of Ojas, maintenance of Vyadhikshamatva, and prevention of recurrent illness. Modern research also supports its role as an immunomodulatory herb, though proper dose, correct botanical identification, standardization, and safety monitoring are necessary, especially because recent reports have discussed possible liver injury associated with unsupervised or misidentified use.